Biophysical Characteristics of Tropical Peatland - Lulie, Melling; Goh, Kah Joo; Lah, Jau Uyo; Alexander Kiew, Sayok; Ryusuke, Hatano (Malaysian Society of Soil Science, 2007)
Based on Jenny’s equation (1941) of soil forming factors i.e. S = f(C, R, B, P, T) with the five soil forming factors, the biotic (B) factor of soil formation is the most multifaceted among them. The biotic factor can be grouped into vegetation, microorganisms, animals and human activities. Vegetation is considered to be the most important facet of the biotic factor. Efforts to explain soil characteristics in terms of the influence of biota are best facilitated by biosequence studies. These studies contain a series of soil profiles across which the biotic soil forming factor varies while other soil forming factors remain constant. Within the context of a biosequence, the effect of changing biotic factor upon any soil property can be assessed quantitatively. For tropical peat, vegetation is both a biotic and parent material for soil forming factors. The elemental composition of soil differs from that of geologic materials in its striking enrichment of carbon and nitrogen compounds relative to most rocks. The organic compounds of the plants are the ultimate sources of this C and N. Plants contribute organic compounds to the soil in a variety of ways, including the senescence or necrosis of tissue, exudation or respiration from the roots, and the liberation of reproductive tissues such as pollen, seeds and fruits. Thus plants that live on the soil both influence soil properties and are influenced by soil properties. And these have been observed on the tropical peat of Sarawak whereby there is an existence of biosequence in each peat basin i.e. different forest types on a peat basin means different soil characteristics caused by different biophysical characteristics of the peat. This biosequence in the peat swamps of Peninsular Malaysia is less highly developed than those in Sarawak (Anderson, 1964). Therefore the objective of this paper is to describe the physical characteristics of the peat in relation to the forest types and its implication to agriculture development especially oil palm cultivation on tropical peat.